SAFETY ASSESSMENT OF AN ORAL RABIES VACCINE BAIT FOR WILD CARNIVORES IN A SERONEGATIVE DOG MODEL - Bulatov, Ye.A.; Koshemetov, Zh.K.; Amanova, Zh.T.; Abitayev, R.T.; Ussembay, A.K.; Sametova, Zh.Zh.; Kondybaeva, Zh.B.; Kurmasheva, A.K.; Mazbayeva, D.M.; Turyskeldy, Sh.S.; Toktyrova, D.S. (Eurasian Journal of Applied Biotechnology, 2025)
Rabies remains one of the most dangerous zoonotic diseases, causing tens of thousands of deaths annually. One of the key challenges in combating rabies is the vaccination of wild carnivores, domestic, and farm animals, which play a crucial role in the circulation of the virus in nature. The aim of the present study was to evaluate the safety and immunogenicity of an oral rabies vaccine in the form of a baited briquette using seronegative dogs as a model. During the experiment, clinical parameters, serological markers, and the behavior of animals following immunization and controlled infection were assessed. The obtained data indicate good vaccine tolerance, high bait acceptance, and the formation of a strong immune response in the vaccinated animals. The oral vaccine did not cause any adverse effects and provided protection against infection in the majority of vaccinated dogs. The results of the study confirm the potential for using this vaccine form in field conditions, both for target and non-target animals.